SitRS XT - Towards Near Real Time Situation Recognition - Franco da Silva, Ana Cristina; Hirmer, Pascal; Wieland, Matthias; Mitschang, Bernhard (Journal of Information and Data Management, 2016)
Nowadays, the Internet of Things gains more and more attention through cheap, highly interconnected hardware devices that are attached with sensors and actuators. This results in an instrumented environment that provides sufficient context information to drive what is called situation recognition. Situations are derived from large amounts of context data, which is difficult to handle. In this article, we present SitRS XT, an extension of our previously introduced situation recognition service SitRS, to enable situation recognition in near real time. SitRS XT provides easy to use situation recognition based on Complex Event Processing, which is highly efficient. The architecture and method of SitRS XT is described and evaluated through a prototypical implementation.